THE CONTENT AND ESSENCE OF DEVELOPING STUDENTS' CREATIVITY IN VOCATIONAL EDUCATIONAL INSTITUTIONS - Rakhmonova Maftuna (Journal Park Publishing, 2025)
This article discusses the content, historical and theoretical foundations of the concept of creativity in the modern education system, as well as the methodology for its development. Based on pedagogical and psychological sources, the specific features of creativity are analyzed and proposals are made for its integration into the educational process.
Keywords: Creativity, content, pedagogy, psychology, creativity, ability, education, upbringing